2013
DOI: 10.1080/01634372.2013.811145
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Families and Staff in Nursing Homes and Assisted Living: Implications for Social Work Practice

Abstract: Nursing homes and residential care/assisted living settings provide care to 2.4 million individuals. Few studies compare the experience of and relationships between family and staff in these settings, despite ongoing family involvement and evidence that relationships are problematic. Data from 488 families and 397 staff in 24 settings examined family involvement and family and staff burden, depressive symptoms, and perceptions; and staff absenteeism and turnover. There were few differences across setting types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…Even though families in LTRC are typically conceptualized as “visitors,” research has suggested that they often engage in a broad range of activities while “visiting,” such as advocating for their relatives; providing, organizing, and managing personal and instrumental care; and keeping their relatives engaged in emotional and social activities (Gladstone et al, 2006; Port et al, 2005; Zimmerman et al, 2013). Such activities extend well beyond “visiting,” and yet, the “visitor” role has rarely been problematized in the literature, and there are few formal policies addressing this kind of family involvement in care work (Levine, Halper, Peist, & Gould, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though families in LTRC are typically conceptualized as “visitors,” research has suggested that they often engage in a broad range of activities while “visiting,” such as advocating for their relatives; providing, organizing, and managing personal and instrumental care; and keeping their relatives engaged in emotional and social activities (Gladstone et al, 2006; Port et al, 2005; Zimmerman et al, 2013). Such activities extend well beyond “visiting,” and yet, the “visitor” role has rarely been problematized in the literature, and there are few formal policies addressing this kind of family involvement in care work (Levine, Halper, Peist, & Gould, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Just over one fifth of the family carers 1 assisting someone in a facility gave over 10 hours of care per week, with more hours provided when a resident was older and had more severe health conditions such as dementia (Turcotte & Sawaya, 2015). These unpaid carers, most of whom are women, provide and manage body care, offer emotional support, promote social engagement, advocate for relatives, oversee the care that staff provide, and contribute resources and ideas to the LTRC community (Davies & Nolan, 2006; Gaugler, 2005; Gladstone, Dupuis, & Wexler, 2006; Keefe & Fancey, 2000; Stadnyk, Chamberlain, Warner, Marie Earl, & Nickerson Rak, 2017; Zimmerman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(13) A study conducted in North Carolina (USA) with 488 families showed that family involvement in the care of relatives with dependency resulted in physical burden and depressive symptoms. (14) Family members of hospitalized children revealed that remaining as a companion in the hospital impairs sleep and rest, bringing physical consequences that can compromise one's health. They reported feeling fatigue and lack of time for self-care.…”
Section: Discussionmentioning
confidence: 99%